Impact of guidance issued during COVID-19 to expand take-home doses of opioid agonist treatment (OAT) in Ireland: protocol for a population-based analysis of prescribing practices and patient outcomes 2018 to 2023 [version 2; peer review: 1 approved, 2 approved with reservations] - Suzi Lyons; Kathleen Bennett; Gráinne Cousins; Louise Durand; Andy O'Hara; Des Crowley; Eamon Keenan (HRB Open Research)
Background It is increasingly suggested that clinical guidelines and practices be updated to permanently expand relaxation around access to opioid agonist treatment (OAT) take-home doses after COVID-19. Despite a risk of OAT drug diversion, flexibility in take-home doses is valued by patients and associated with improved quality of life and retention. However, few studies have examined the effects of changes to take-home dose policies on prescribing practices and patient outcomes, with mixed results. Aims This protocol relates to three inter-related studies. The first study will examine the impact of guidance issued on March 13th 2020 to all clinicians involved in the delivery of OAT to give the maximum number of take-home doses having given due consideration to the safety of the patient, on prescribing practices for take-home doses of methadone and buprenorphine in primary care. The second study will examine the association between increased take-home doses of OAT following March 13th 2020 guidance and treatment discontinuation in primary care. The third study will examine methadone-related deaths in Ireland before and after the guidance issue, and whether methadone-related deaths varied by whether the deceased was on OAT treatment at the time of death. Methods Retrospective observational studies will be carried out. The first study will use a time series design to examine changes in prescribing practices of take-home doses. The second study will use a retrospective cohort study design with proportional hazard Cox models to evaluate the association between increased take-home doses and treatment discontinuation. The third study will use a repeated cross-sectional study design with interrupted time series analysis, stratified by OAT treatment status, to assess changes in methadone-related deaths. Discussion It is anticipated that the studies will generate evidence with potential to inform both clinical and policy decision making with respect to take-home dosing of OAT.